ANTI-OBESITY EFFECT OF CANNABIS SATIVA SEED FLOUR FROM KHLALFA OF TAOUNATE REGION (NORTHERN OF MOROCCO) IN HIGH CALORIC DIET-INDUCED OBESE MICE - BOUARFA, MOUNA; SOUIRTI, ZOUHAIR; CERRUTI, PIERFRANCESCO; AVELLA, MAURIZIO; FARAH, ABDELLAH; BOUSTA, DALILA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the present study was to evaluate the anti-obesity activity of Cannabis sativa seed Flour (CSSF) on obese mice. Methods: The experiment process was carried out in 8 weeks. In this time, three groups of animals were adopted: High caloric diet control group (HCD), group treated with 100 mg/kg of CSSF, group treated with 200 mg/kg of CSSF, and normal diet control group (ND). Then, the histopathological and biochemical parameters analysis has been realized at the end of the experiment. Results: As a result, body weight gain, epididymal, and perirenal adipose tissue decreased in the CSSF (Cannabis sativa seed Flour) group in both doses (100 mg/kg and 200 mg/kg) compared to the HCD. CSSF lowered serum glucose level elevated by HCD. For lipid profiles, total cholesterol (TC), HDL-cholesterol, LDL-cholesterol, and triglycerides (TG) significantly decreased in the CSSF group. The histopathological results of this study showed a regenerative effect of CSSF on the kidney and liver tissues. Conclusion: It is concluded from the present study that CSSF can be used as a natural anti-obesity agent.